A gene-specific RNA enrichment protocol for nanopore direct-RNA sequencing - Maja Bele Dyrendalsli; Cecilie Løkke; Christer Einvik (PLoS ONE, 2026)
Oxford Nanopore direct-RNA sequencing, a third-generation sequencing technology, allows for the analysis of native RNA molecules in their natural cellular state. However, cellular RNA is predominantly composed of ribosomal RNA and transcripts from ubiquitously expressed housekeeping genes, which limits the coverage of transcripts from lowly expressed genes. To address this limitation, targeted sequencing can be employed to enrich read coverage by focusing specifically on genes of interest. Here, we present a step-by-step protocol for gene-specific RNA enrichment followed by Oxford Nanopore direct-RNA sequencing. The enrichment protocol utilizes biotinylated DNA capture probes complementary to the target gene. Following in-solution hybridization of probes to total RNA, a series of stringent washes is applied before elution of the enriched RNA sample. The protocol describes all steps from isolation of cellular total RNA to bioinformatic analyses of raw sequencing data. As a proof of concept, capture probes were designed to specifically enrich all RNA species encoded by the MYCN oncogene. The enrichment protocol successfully isolated RNAs from the MYCN gene, achieving a purification factor of 4.8 × 10 3 . Direct-RNA sequencing of the enriched RNA sample revealed that 65% of the primary mapped reads aligned to MYCN transcripts. We also include a more thorough analysis of the most abundant non-target mapped reads and unmapped reads. This protocol proves to be highly effective in removing unwanted RNA species, delivering robust enrichment for the target gene, and significantly enhancing the efficiency of long-read direct-RNA sequencing.